2013
DOI: 10.4103/0976-500x.114597
|View full text |Cite
|
Sign up to set email alerts
|

N -acetyl cysteine in clomiphene citrate resistant polycystic ovary syndrome: A review of reported outcomes

Abstract: Clomiphene citrate (CC) has been the gold-standard drug for ovulation induction in polycystic ovary syndrome (PCOS), but still CC resistance is seen in approximately 15-40% in women with PCOS. N-acetyl cysteine (NAC), a safe and cheap drug available in the market many years ago as mucolytic agent, was found to have a role in infertility management. Recently, some reports discussed the possible beneficial effects of NAC on ovulation. The biological properties of the NAC make this drug a potential candidate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The superiority of metformin+clomiphene over NAC+clomiphene in terms of ovulation and pregnancy was demonstrated in one RCT . A recent review of clinical studies of the results of NAC for the induction of ovulation in CCR‐PCOS women showed both positive and negative results .…”
Section: Discussionmentioning
confidence: 98%
“…The superiority of metformin+clomiphene over NAC+clomiphene in terms of ovulation and pregnancy was demonstrated in one RCT . A recent review of clinical studies of the results of NAC for the induction of ovulation in CCR‐PCOS women showed both positive and negative results .…”
Section: Discussionmentioning
confidence: 98%
“…12 Many studies tried to combine another drug to CC to increase its efficacy. 13 Others replaced it by an alternative medical or surgical treatment. Gonadotrophins therapy (GTs) is considered the best second line as it doesn't affect ovarian reserve and carries no risks of peritubal or periovarian adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Second-line treatments for infertile women with CCR-PCOS include gonadotrophins, laparoscopic ovarian diathermy (LOD) and other oral agents, such as aromatase inhibitors, N-acetylcysteine (NAC), and other insulin sensitizers (Abu Hashim et al, 2013;ESHRE/ASRM, 2008;Franik et al, 2014;Saha et al, 2013;Tang et al, 2012). Although many RCT have investigated the efficacy of metformin plus different second-line treatment options in CCR-PCOS patients, only two RCT compared metformin monotherapy with LOD with conflicting results.…”
Section: Metformin Plus Clomiphene Citrate Versus Other Second-line Tmentioning
confidence: 99%